Penguasaan Konsep Siswa pada Model Pembelajaran Interactive Demonstration disertai Formative Feedback - Suryaningsasi Suryaningsasi; Sentot Kusairi; Hari Wisodo (Graduate School of Universitas Negeri Malang, 2018)
Abstract: This research was aimed to analyze the mastery of the concept of pressure on interactive demonstration learning model with formative feedback. The study involved 45 students of class VIII SMP Negeri 2 Rembang. The learning process is designed using the interactive learning demonstration stages in which it integrates with formative feedback. Tests form two-tiers as a measure of mastery of student concepts given before and after learning. The test results were analyzed qualitatively and quantitatively. The result of the analysis shows that the learning has an influence on the mastery of student concept with very strong category (very strong). The result of the improvement of students' master comprehension score before and after learning is in the medium category. Students experience an increased level of mastery of the concept from low to high on cognitive indicators of inhibiting (C1), and an increase in concept mastery level from low to moderate on understanding indicators (C2). Overall score indicator mastery of the concept of pressure. In the cognitive indicators of understanding (C3) and analysis (C4) has increased in the low category.Abstrak: Penelitian ini bertujuan untuk menganalisis penguasaan konsep tekanan pada model pembelajaran interactive demonstration disertai formative feedback. Penelitian ini melibatkan 45 siswa kelas VIII SMP Negeri 2 Rembang. Proses pembelajaran dirancang menggunakan tahapan-tahapan pembelajaran interactive demonstration yang didalamnya terintegrasikan dengan formative feedback. Tes bentuk two-tiers sebagai alat ukur penguasaan konsep siswa yang diberikan sebelum dan sesudah pembelajaran. Hasil tes dianalisis secara kualitatif dan kuantitatif. Hasil analisis menunjukkan bahwa pembelajaran tersebut memiliki pengaruh terhadap penguasaan konsep siswa dengan kategori sangat kuat (very strong). Hasil peningkatan skor penguasaan konsep siswa sebelum dan setelah pembelajaran berada pada kategori sedang. Siswa mengalami peningkatan level penguasaan konsep dari rendah menuju tinggi pada indikator kognitif mengingat (C1), dan mengalami peningkatan level penguasaan konsep dari rendah menuju sedang pada indikator memahami (C2). Secara keseluruhan, skor indikator penguasaan konsep tekanan. Pada indikator kognitif memahami (C3) dan analisis (C4) mengalami peningkatan yang masih dalam kategori rendah.